Morphology and Morphometric Study of Left and Right Harderian Glands in Duck and Broiler - Kamel, Makarem Mustafa; Zghair, Fatimah Swadi; Al-Abdula, Maha Abdul-Hadi Abdul-Rida (American Journal of Biomedicine and Pharmacy, 2025)
The aim of study is to determine the comparative morphological morphometric features of harderian gland of two species of birds, the birds were broiler chicken and, duck were taken (10 birds for each species) the birds scarified then the dissected and removed the gland that grossly examined and morphometric measurement (length and width) of gland were done. The study noticed the color of chicken glands were light brown to pink and they are different in size and shape in each other. in was elongated and small, the smaller one was in duck its teardrop in shape.